A companion to the Poema de mio Cid - Zaderenko, Irene; Montaner Frutos, Alberto, 1963-; Mahoney, Peter, 1979- (Brill's companions to Mediaeval philology, 2018)
This volume brings together a number of distinguished scholars in the field of Poema de mio Cid studies. It provides an informed introduction to key literary aspects of the poem, and thoroughly examines many of the complex issues that are crucial for a comprehensive understanding of the work (historical context, ideological motivations, prosification in medieval chronicles, the poem's place in the canon of Spanish literature). Equally important are the new findings that have been put forward since the 1970s, when scholars started to challenge Ramón Menéndez Pidal's theories that had dominated the philological discourse since the beginning of the twentieth century. Contributors are Matthew Bailey, Simon Barton, Francisco Bautista, Juan Carlos Bayo Julve, Federico Corriente, Leonardo Funes, Luis Galván, Fernando Gómez Redondo, Eukene Lacarra Lanz, Salvatore Luongo, Georges Martin, Alberto Montaner, Javier Rodríguez Molina, Mercedes Vaquero, Roger Wright, and Irene Zaderenko.